Going digital and staying qualitative : some alternative strategies for digitizing the qualitative research process - Brown, David
Qualitative research is rapidly changing as a result of the deployment of Information Technologies (IT). Practices that have taken decades to evolve are being redefined by contemporary computing power. Since the 1990s one of the buzzwords in the computing, communications and technology industries has been "Digital Convergence"—the digitizing of different media forms. Digitization is an ongoing phenomenon, constantly developing and evolving the way we communicate and interact—a product of reflexive modernity, but what does it mean for the qualitative research as a process and how might we make use of it? The paper responds to these questions by making some practical suggestions for digitized strategies and processes that qualitative researchers might draw on eclectically in order to express freely their own creative abilities, which in turn facilitates the opening up of new idiographic avenues for exploring and disseminating subjective experience. In so doing the paper juxtaposes the alternative manual nature of these strategies with other developments that are increasingly orientated towards semi-automated computerized data processing.